Seasonal prevalence of arthropoda and helminth parasites in sheep (Ovis aries (Bangladesh Journal of Zoology, 2015)
The present investigation was carried out to determine the prevalence of arthropoda and helminth parasites in sheep at Azimpur, Dhaka during February, 2012 to January, 2013. A Total of 60 hosts were examined and about 71.67% sheep were found to be infested with arthropod parasites. In sheep two species of arthropod parasites, Linognathus vituli (61.67%) and Damalinia caprae (68.33%) were identified as ecto-parasites. The prevalence of ectoparasites was higher during summer (85%), followed by winter (75%) and rainy (55%). The higher intensity was also recorded in summer (325.17±1.92). Lambs were found more susceptible (85.71%) than adult (80.95%) and young (56%) sheep and higher in female (77.27%) than in male (68.42%). Twelve species of helminth parasites were identified, of them, 3 trematodes, 3 cestodes and 6 nematodes, highest prevalence was shown by Strongyloides sp (71.67%) and lowest by Dictyocaulus sp. (3.33%); found comparatively higher in adults (85.71%) than in young (80%) and 28% in lambs. The male sheeps were more susceptible (81.58%) to helminth infection than female (72.73%). Prevalence of helminthes was found higher in winter (95%) season. The value of co-efficient of correlation between the prevalence and intensity of infestation of ectoparasites and helminth parasites in sheep were 0.95 and 0.978 respectively. In both cases these two variables differed significantly (P